Body weight management and safety with efpeglenatide in adults without diabetes: A phase II randomized study. Issue 11 (13th August 2019) - Pratley, Richard E.; Kang, Jahoon; Trautmann, Michael E.; Hompesch, Marcus; Han, OakPil; Stewart, John; Sorli, Christopher H.; Jacob, Stephan; Yoon, Kun‐Ho
Abstract: Aim: To evaluate the safety of efpeglenatide, a long‐acting glucagon‐like peptide‐1 receptor agonist (GLP‐1RA), and its effects on body weight management in adults without diabetes. Materials and methods: In this phase II, randomized, placebo‐controlled, double‐blind trial, participants with a body mass index (BMI) ≥30 kg/m 2 or ≥27 kg/m 2 with comorbidity were randomized 1:1:1:1:1 to efpeglenatide (4 mg once weekly, 6 mg once weekly, 6 mg once every 2 wk, or 8 mg once every 2 wk; n = 237) or placebo (n = 60) in combination with a hypocaloric diet. The primary endpoint was body weight change from baseline after 20 wk of treatment, assessed using a mixed‐effect model with repeated measures with an unstructured covariance matrix over all post‐screening visits; treatment comparisons were based on least squares mean estimates. Results: Over 20 wk, all doses of efpeglenatide significantly reduced body weight from baseline versus placebo ( P < 0.0001), with placebo‐adjusted reductions ranging between −6.3 kg (6 mg once every 2 wk) and −7.2 kg (6 mg once weekly). Greater proportions of efpeglenatide‐treated participants had body weight loss of ≥5% or ≥10% versus placebo ( P < 0.01, all comparisons). Efpeglenatide led to significant improvements in glycaemic variables (fasting plasma glucose and glycated haemoglobin) and lipid profiles (cholesterol, triglycerides) versus placebo. Rates of study discontinuations as a result of adverse events ranged from 5% to 19% with efpeglenatide. Gastrointestinal effects were the most common treatment‐emergent adverse events. Conclusions: Efpeglenatide once weekly and once every 2 wk led to significant body weight reduction and improved glycaemic and lipid variables versus placebo. It was also well tolerated for weight management in adults without diabetes.